Features of the choice of the method of construction work in the conditions of reconstruction of buildings - Savyovsky, V.; Solovey, D.; Bronevitsky, A.; Ovchinnikov, O. (Ways to Improve Construction Efficiency, 2020)
Revitalization of industrial buildings is a fairly common worldwide construction practice. In Ukraine, this process is only gaining momentum. Kiev is the leader in the number of successful revitalization projects among Ukrainian cities. Revitalization is one of the elements of reconstruction and, therefore, it is also characterized by a number of specific features, which do not allow the use of traditional technology and organization of work. The specified features of reconstruction of objects determine the optimal version of the technology and the organization of construction and installation works, thus significantly affecting the level of technical and economic indicators of reconstruction as a whole. The influence of these features occurs throughout the entire duration of the work, while the process of their influence can be complex and have varying degrees. The problem is aggravated by the fact that the above features are constantly changing, while complicating the conditions for the execution of work, which significantly affects the adoption of organizational and technological decisions for the execution of works, and in some cases architectural and structural decisions. Therefore, the urgent task is to conduct a balanced analysis of the conditions of the reconstruction in the design and engineering preparation of the reconstruction. It is important to consider in advance the probable effect of reconstruction features for forecasting and effective management of the resources provided for the reconstruction of buildings. Taking into account the influence of the considered features will allow us to develop effective organizational and technological solutions and improve them at other facilities in similar conditions. The implementation of the obtained solutions will make it possible to justify the feasibility of reconstructing objects in difficult urban conditions, reduce labor intensity, increase the economic efficiency of construction and installation works, speed up the construction process, and provide solutions to important applied problems in the development of urban space.